Beyond the Market: The Role of Constitutions in Health Care System Convergence in the United States of America and the United Kingdom. Issue 4 (December 2014) - Fletcher, Jamie; Marriott, Jane
<x xml:space="preserve">Abstract</x> Health care reform in the United States (US) and United Kingdom (UK) has resulted in the cross‐fertilization of policy. The "new" health care models adopted by the two jurisdictions utilize free market principles for reasons of quality, efficiency, and cost, but also feature characteristics of a state‐run model, through the provision of a safety net for citizens and a buffer against the commodification of health. In this sense, the health care systems of the US and UK are more congruent than they were. Here we identify two distinct narratives that emerge from health care reform undertaken in these jurisdictions. The "revolutionary" narrative views the reforms as fundamental change whilst the "evolutionary" narrative accepts them as natural development. We argue that neither the revolutionary nor the evolutionary narrative adequately characterizes the reforms undertaken in health care because neither takes sufficient account of the broader setting in which reform has occurred. In seeking to examine and explain the jurisdictions' apparent drive to the middle, we propose a distinctive evolutionary narrative, that of "convergence, " which, as well as adopting a less parochial perspective on developments in health care policy and provision, also situates the reforms politically, constitutionally, and comparatively.